2009
DOI: 10.1182/blood-2009-01-198937
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for chronic lymphocytic leukemia based on expression of the SV40 large T antigen

Abstract: IntroductionB-cell chronic lymphocytic leukemia (B-CLL), 1,2 the most common leukemia in the Western world, is characterized by the accumulation of a monoclonal population of mature B cells that aberrantly express CD5. 3,4 The clinical course of CLL is extremely heterogeneous: whereas some patients survive more than a decade with stable disease, others die of the disease within months despite aggressive treatment. This heterogeneity is associated with variability in the expression pattern of a number of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…The transgenic mice IgH.TEm have been described previously (32), and their natural history of malignant progression has been monitored ( Supplementary Fig. S1) in about 150 mice.…”
Section: Micementioning
confidence: 99%
“…The transgenic mice IgH.TEm have been described previously (32), and their natural history of malignant progression has been monitored ( Supplementary Fig. S1) in about 150 mice.…”
Section: Micementioning
confidence: 99%
“…14 ter Brugge et al have shown that mice expressing the SV40 Tag reveal a normal B cell development but, upon aging, these mice show an accumulation of monoclonal CD5(ϩ) B cells and have a CLL-like phenotype. 15 MCPyV is highly related to the lymphotropic polyomavirus (LPV) of African green monkey that is known to infect B lymphocytes. 1,16 The presence of MCPyV in peripheral blood at low copy number has been demonstrated recently also suggesting lymphotropism of MCPyV.…”
Section: Introductionmentioning
confidence: 99%
“…(35) Given the low toxicity profile suggesting ease of combining with standard chemotherapy, as well as early single agent efficacy signals, members of this pathway represent an extremely promising target in DLBCL, and combinations of these agents may yield the best results in appropriate subsets of patients defined by gene expression analyses. (36)…”
Section: On the Horizonmentioning
confidence: 99%